The effectiveness of proposed slope rehabilitation methods on the slope stability in Jalan Damansara [electronic resource] - 639263 Lee, Khai Lin, 1983- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2015)
Thesis (Sarjana (Kejuruteraan Awam - Geoteknik))- Universiti Teknologi Malaysia, 2015